Use of Chitosan-PVA Hydrogels with Copper Nanoparticles to Improve the Growth of Grafted Watermelon - González Gómez, Homero (Molecules, 2017)
Modern agriculture requires alternative practices that improve crop growth without negatively affecting the environment, as resources such as water and arable land grow scarcer while the human population continues to increase. Grafting is a cultivation technique that allows the plant to be more efficient in its utilization of water and nutrients, while nanoscale material engineering provides the opportunity to use much smaller quantities of consumables compared to conventional systems but with similar or superior effects. On those grounds, we evaluated the effects of chitosan-polyvinyl alcohol hydrogel with absorbed copper nanoparticles (Cs-PVA-nCu) on leaf morphology and plant growth when applied to grafted watermelon cultivar ‘Jubilee’ plants. Stomatal density (SD), stomatal index (SI), stoma length (SL), and width (SW) were evaluated. The primary stem and root length, the stem diameter, specific leaf area, and fresh and dry weights were also recorded. Our results demonstrate that grafting induces modifications to leaf micromorphology that favorably affect plant growth, with grafted plants showing better vegetative growth in spite of their lower SD and SI values. Application of Cs-PVA-nCu was found to increase stoma width, primary stem length, and root length by 7%, 8% and 14%, respectively. These techniques modestly improve plant development and growth.